Edukasi Corona Virus Desease 19 (Covid-19) Melalui Program STIKES RS Baptis Melayani Dengan Kasih Kepada Siswa SLB Putera Asih Kediri - Kili Astarani; Dewi Ika Sari; Aries Wahyuningsih; Maria Anita Yusiana (Pelita Medika, 2021)
Background : Covid-19 is an infectious disease caused by the SARS-CoV 2 virus. Since it was first announced in Indonesia, the number of COVID-19 cases has increased from time to time so it requires attention. In practice during the pandemic, the management of COVID-19 requires the cooperation of all stakeholders to handle it. Efforts are needed to prevent and contain the spread of the corona virus. Prevention efforts can be carried out by carrying out various activities, one of which is outreach activities to be able to provide scientific information to all levels of society regarding the corona virus outbreak in Indonesia and at the Putera Asih Kediri Special School in particular. Method : The number of students and parents or families participating in Corona Virus Disease 19 (Covid-19) Education through the STIKES Program Baptist Hospital Serves With Love is 24 people. Results : The average value of the pretest was 68.06 and after education the average value of the posttest increased by 79.44. There was an increase of 11.39. This is in line with the expectations of the service team, namely an increase in students' understanding of the corona virus disease 19. Conclusion: Educational activities carried out can increase the understanding of Putera Asih Special School students about Corona Virus Disease-19